2021
DOI: 10.1093/mutage/geab004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic damage in lymphocytes of lung cancer patients is correlated to the composition of the respiratory tract microbiome

Abstract: Recent findings indicate that the microbiome may have significant impact on the development of lung cancer by its effects on inflammation, dysbiosis or genome damage. The aim of this study was to compare the sputum microbiome of lung cancer (LC) patients with the chromosomal aberration (CA) and micronuclei (MN) frequency in peripheral blood lymphocytes. In the study, the taxonomic composition of the sputum microbiome of 66 men with untreated LC were compared to 62 control subjects with respect to CA and MN fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…With our established metaproteomics platform, we identified several lung cancer-associated bacteria from the genus to the class level that is consistent with previous sequencingbased studies [9,[61][62][63][64][65][66] and revealed novel lung cancerrelated bacteria that were underestimated by conventional methods. Through an independent cohort validation, 7 species were confirmed to be lung cancer associated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…With our established metaproteomics platform, we identified several lung cancer-associated bacteria from the genus to the class level that is consistent with previous sequencingbased studies [9,[61][62][63][64][65][66] and revealed novel lung cancerrelated bacteria that were underestimated by conventional methods. Through an independent cohort validation, 7 species were confirmed to be lung cancer associated.…”
Section: Discussionsupporting
confidence: 86%
“…We then conducted the linear discriminant effect size (LEfSe) analysis to explore marked differences of bacteria between the two groups (Figure 5(b)). Genus Fusobacterium and Neisseria, family Neisseriaceae and Actinomycetaceae, and order Burkholderiales were characteristic bacteria in lung cancer, while decreased genus Actinomyces and class Spirochaetia was found in lung cancer, which corroborates the findings in previous sequencing-based studies [9,[61][62][63][64][65][66].…”
Section: Identification Of Lungsupporting
confidence: 90%
“… 4 , 27 The relative abundance of a lung cancer-associated oral-related bacteria, Streptococcus , tended to be reduced in the subset of patients who took CBM588 compared with the subset who did not. 29 , 32 These results suggest that the presence of a live biotherapeutic bacterium CBM588 in the gut of cancer patients may provide a beneficial impact on gut commensals.
Figure 7.
…”
Section: Resultsmentioning
confidence: 92%
“…Since pneumoconiosis is associated with the risk of cancer [ 7 ], it is interesting to consider the presence of Streptococcus in the respiratory tract of lung cancer patients. We recently reported a significant increase in the representation of Streptococcus , Bacillus , Gemella, and Haemophilus in the sputum of lung cancer patients compared to control subjects [ 48 ]. In addition to a significant increase in Streptococcus , we also observe an increase in the representation of the genera Bacillus and Gemella in the sputum of miners with CWP compared to control subjects ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%